PENGARUH RETURN ON ASSETS RETURN ON EQUITY DEBT TO EQUITY RATIO DAN BOOK VALUE PER SHARE TERHADAP HARGA SAHAM - Putri, Nyayu Khairani; Septianti, Dian (Universitas Muhammadiyah Palembang, 2020)
The purpose in this research is to explain the influence Return On Assets (ROA), Return On Equity (ROE), Debt to Equity Ratio (DER), and Book Value per Share (BVS) on stock price in the manufacture sector at Indonesian Stock Exchange. Sample in this study were 50 companies in manufacture sector in period 2015-2017. Data were chosen by using purposive sampling. Data were analyzed by using multiple regression analysis. The result of the research showed; ROA and BVS has positive and significant effect on stock price. ROE have negative but not significant effect on stock price. DER has positive but not significant effect on stock price.